2014
DOI: 10.1016/j.aquatox.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect-directed analysis for estrogenic compounds in a fluvial sediment sample using transgenic cyp19a1b-GFP zebrafish embryos

Abstract: Xenoestrogens may persist in the environment by binding to sediments or suspended particulate matter serving as long-term reservoir and source of exposure, particularly for organisms living in or in contact with sediments. In this study, we present for the first time an effect-directed analysis (EDA) for identifying estrogenic compounds in a sediment sample using embryos of a transgenic reporter fish strain. In the tg(cyp19a1b-GFP) transgenic zebrafish strain, the expression of GFP (green fluorescent protein) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 50 publications
0
33
0
1
Order By: Relevance
“…When instead the aim of multiple methods was to analyse different aspects of the same bioactivity or toxicity mechanism, there was the prevalence of tiered approach biotesting [19,39,45]. When applied in screening phase, zebrafish bioassays aimed to identify active fractions by organism-level endpoints, which were later further investigated by additional methods with zebrafish [52] or with other experimental models [19,45]. As an example, zebrafish bioassays were applied to screen extracts and fractions for anti-angiogenic effects, followed by further investigations on human cells and transgenic zebrafish embryos [19].…”
Section: Biotesting Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…When instead the aim of multiple methods was to analyse different aspects of the same bioactivity or toxicity mechanism, there was the prevalence of tiered approach biotesting [19,39,45]. When applied in screening phase, zebrafish bioassays aimed to identify active fractions by organism-level endpoints, which were later further investigated by additional methods with zebrafish [52] or with other experimental models [19,45]. As an example, zebrafish bioassays were applied to screen extracts and fractions for anti-angiogenic effects, followed by further investigations on human cells and transgenic zebrafish embryos [19].…”
Section: Biotesting Strategymentioning
confidence: 99%
“…[36,53,[55][56][57]) or a combination of methods (e.g. [44,52]) to evaluate endpoints in zebrafish. Other studies applied methods with additional experimental models, mostly cell-based (e.g.…”
Section: Biotesting Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found most estrogenic activity in polar fractions of log K ow 2-4 of effluent, river water, and sediment extracts (Creusot et al 2013;Grung et al 2011;Houtman et al 2004;Smital et al 2011). Fetter et al (2014 further suggested alkylphenols and estrone as Water F22 F16 F15 F14 F12 F10 F9 F8 F7 F5 F3 F2 S1 S2 S5 S8 S9 S10 S11 The present study did demonstrate that polar and mid-polar compounds such as E1, E2, and BPA are widely present in both water and sediment samples.…”
Section: Effect-directed Analysismentioning
confidence: 92%
“…In addition to the collection of legacy data on historical uses of sites, one of the solutions would be, to intensify the coupling between soil biomonitoring and 12 analytical tools and methods, where health effects are observed on soil fauna and flora. This can be done for instance with Effect Directed Analysis which aims to identify the compounds causing these effects after reducing sample complexity by combining biotests with fractionations (Fetter et al, 2014). More generally, further (eco)toxicological research would be necessary to better assess human health risk particularly on chemical forms of contaminants and their toxicity related to environmental and biological conditions.…”
Section: Development Of New Tools For a Better Assessment Of Soil Conmentioning
confidence: 99%